2006
DOI: 10.1002/mrd.20615
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific windows for high mRNA expression of DNA methyltransferases 1 and 3A and methyl‐CpG‐binding domain proteins 2 and 4 in human fetal gonads

Abstract: DNA methyltransferases (DNMTs) and 5-methyl-CpG-binding domain proteins (MBDs) are involved in the acquisition of parent-specific epigenetic modifications in human male and female germ cells. Reverse Northern blot analyses demonstrated sex-specific differences in mRNA expression for the maintenance DNMT1 and the de novo DNMT3A in developing testis and ovary. In fetal testis DNMT1 and DNMT3A expression peaked in mitotically arrested spermatogonia around 21 weeks gestation. In fetal ovary transcriptional upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Thus, despite the lack of total quiescence, human fetal gonocytes present a period of minimal proliferation similar to the quiescence phase observed in rodents. Moreover, it is interesting to note that the late gestation period of low proliferation in human fetal gonocytes partially overlaps with the phase of highest DNA methyl transferase expression (GW21-GW29), strikingly reminiscent of the high DNA methylation activities observed during late gestation in rodent gonocytes (Galetzka et al 2007). In marmoset, in which gestation lasts 22 weeks, similar fluctuations in proliferation rates were observed, with maximal proliferation at GW11-GW14, a decrease at GW15-GW16, followed by an increase to 40% of proliferating gonocytes at GW17-GW20, and a return to a lower rate until 6 weeks after birth (Mitchell et al 2008).…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 98%
“…Thus, despite the lack of total quiescence, human fetal gonocytes present a period of minimal proliferation similar to the quiescence phase observed in rodents. Moreover, it is interesting to note that the late gestation period of low proliferation in human fetal gonocytes partially overlaps with the phase of highest DNA methyl transferase expression (GW21-GW29), strikingly reminiscent of the high DNA methylation activities observed during late gestation in rodent gonocytes (Galetzka et al 2007). In marmoset, in which gestation lasts 22 weeks, similar fluctuations in proliferation rates were observed, with maximal proliferation at GW11-GW14, a decrease at GW15-GW16, followed by an increase to 40% of proliferating gonocytes at GW17-GW20, and a return to a lower rate until 6 weeks after birth (Mitchell et al 2008).…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 98%
“…Galetzka et al demonstrated that the sex-specific time windows for concomitant upregulation of DNMT1, DNMT3A, MBD2, and MBD4 are associated with prenatal re-methylation of the human male and female germ line. This may provide an important clue for the molecular mechanisms to parent-specific epigenetic modifications in human male and female germ cells [103].…”
Section: Many Facets Of the Methyl-cpg-binding Protein-mbd2mentioning
confidence: 99%
“…Most of the vertebrate genome is normally packaged as transcriptionally repressive chromatin of the same kind found in "Pericentromeric Heterochromatin" regions. This type of chromatin is heavily methylated, and the identities of the chromatin associated protein complexes that might link DNA-methylation to transcriptional silencing have been discovered over the past few years (reviewed in [34,39,40,57,103,[120][121][122][123][124][125][126][127]). In these transcriptionally silent regions, DNA is packaged into compacted nucleosomes that contain deacetylated histones, deacetylated H3 in particular.…”
Section: Interpreting Demethylation Signals In Cellsmentioning
confidence: 99%
“…Notably, the remaining N-terminal amino acids have been implicated in DNA binding [32]; moreover, the truncated protein p.Q237X resembles isoform DNMT3A3 (166 amino acids; Fig. 1b), which is catalytically inactive and may display a regulatory function by targeting full-length DNMT3A to the chromatin [33,34]. This isoform is not ubiquitously expressed; instead, it is present in developing gonads, testicular cells and resting fibroblasts.…”
Section: The Dnmt3a Proteinmentioning
confidence: 99%